2016
DOI: 10.1091/mbc.e16-06-0362
|View full text |Cite
|
Sign up to set email alerts
|

The role of gigaxonin in the degradation of the glial-specific intermediate filament protein GFAP

Abstract: Gigaxonin is an E3 ubiquitin ligase adaptor that facilitates proteasomal degradation of GFAP in astrocytes. Gigaxonin is similarly involved in the degradation of some but not all disease-linked forms of GFAP. This degradation is mediated by a direct interaction of gigaxonin with GFAP and involves the proteasome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…This effect is so robust that it also enables the clearance of vimentin bundles in fibroblasts from patients and GAN mouse embryonic fibroblasts (Mahammad et al, 2013). From this initial key findings, the potent effect of Gigaxonin has been extended to various IFs of the nervous system, and is now confirmed in normal cells [neurons in Mahammad et al (2013), Israeli et al (2016) and astrocytes in Lin et al (2016)], but also in disease context [GAN iPSC-derived neurons in Johnson-Kerner et al (2015a), and GAN DRG in Israeli et al (2016)]. To understand this unique action on multiple IFs proteins, that constitute the cytoskeleton of tissues throughout the body, it is important to introduce the structure of IF proteins.…”
Section: Gigaxonin Is a Universal Regulator Of The Intermediate Filammentioning
confidence: 86%
See 3 more Smart Citations
“…This effect is so robust that it also enables the clearance of vimentin bundles in fibroblasts from patients and GAN mouse embryonic fibroblasts (Mahammad et al, 2013). From this initial key findings, the potent effect of Gigaxonin has been extended to various IFs of the nervous system, and is now confirmed in normal cells [neurons in Mahammad et al (2013), Israeli et al (2016) and astrocytes in Lin et al (2016)], but also in disease context [GAN iPSC-derived neurons in Johnson-Kerner et al (2015a), and GAN DRG in Israeli et al (2016)]. To understand this unique action on multiple IFs proteins, that constitute the cytoskeleton of tissues throughout the body, it is important to introduce the structure of IF proteins.…”
Section: Gigaxonin Is a Universal Regulator Of The Intermediate Filammentioning
confidence: 86%
“…This interaction seems to be direct, as assessed by ELISA assay using recombinant vimentin proteins. Accordingly, additional studies showed that other IF types can be found in Gigaxonin immunocomplexes in HEK cells and astrocytes (Johnson-Kerner et al, 2015b;Lin et al, 2016). Interestingly, the potent action of Gigaxonin has been confirmed for keratin and GFAP, mutated and aggregating, respectively in the skin disease EBS and Alexander disease (Lin et al, 2016;Buchau et al, 2018).…”
Section: Gigaxonin Is a Universal Regulator Of The Intermediate Filammentioning
confidence: 93%
See 2 more Smart Citations
“…At 48 hours after transfection, cells were processed for immunofluorescence microscopy as described previously [32]. The primary antibodies used in this study were listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%